2002
DOI: 10.1021/ja020236y
|View full text |Cite
|
Sign up to set email alerts
|

The Electronic Influence of Ring Substituents and Ansa Bridges in Zirconocene Complexes as Probed by Infrared Spectroscopic, Electrochemical, and Computational Studies

Abstract: The electronic influence of unbridged and ansa-bridged ring substituents on a zirconocene center has been studied by means of IR spectroscopic, electrochemical, and computational methods. With respect to IR spectroscopy, the average of the symmetric and asymmetric stretches (nu(CO(av))) of a large series of dicarbonyl complexes (Cp(R))(2)Zr(CO)(2) has been used as a probe of the electronic influence of a cyclopentadienyl ring substituent. For unbridged substituents (Me, Et, Pr(i), Bu(t), SiMe(3)), nu(CO(av)) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
189
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(211 citation statements)
references
References 80 publications
(88 reference statements)
21
189
0
Order By: Relevance
“…It has been reported that the modification in nature and number of substituents on a cyclopentadienyl ring [15][16][17][18]14,19] may directly affect the catalytic activity and/or the stereoselectivity [20], allowing the use of these metallocenic catalysts in industrial processes on a macroscale level, registering catalytic activity values similar or superior to those obtained with the conventional Ziegler-Natta heterogeneous catalysts [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the modification in nature and number of substituents on a cyclopentadienyl ring [15][16][17][18]14,19] may directly affect the catalytic activity and/or the stereoselectivity [20], allowing the use of these metallocenic catalysts in industrial processes on a macroscale level, registering catalytic activity values similar or superior to those obtained with the conventional Ziegler-Natta heterogeneous catalysts [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…[8] Addition of one methyl group to the ancillary cyclopentadienyl ligands (e.g. Cp*Cp Me4 to Cp* 2 ) correlates to a three-fold increase in the acidity of the distant N À H amide proton (Table 1, entries 1-3).…”
mentioning
confidence: 99%
“…The electronic influence of ring substituents and ansa-bridges in zirconocene complexes has been investigated by IR spectroscopy and supported by DFT calculations. 54 The syntheses of new titanium, zirconium, and hafnium() ansa-bridged metallocenes containing a GeMe 2 bridge, 55 SiMe 2 bridged unsymmetrical ansa-zirconocene complexes, 56 and ansa-titanocene that contain bridging C 5 and C 8 long aliphatic chains 57 have been reported. New indenyl-fluorenyl ansa-zirconocenes such as 5 have been used to regioselectively introduce allyl alcohol into non-polar polyolefins.…”
Section: Titanium Zirconium Hafniummentioning
confidence: 99%